The Paracas phenomenon: state of the art and a model of social explanation - Tantaleán, Henry (2021)
This article presents a synthesis of the main investigations and archaeological evidence related to the Paracas phenomenon of the southern Peruvian coast, which developed during much of the first millennium before our era (800-200 BC). The main investigations, the chronology, the territory covered and the main settlements associated with the material culture linked to this social phenomenon are presented and discussed. Finally, a model of social explanation is presented to understand the social dynamics that allowed the appearance of what is known in archaeological literature as the «Paracas Culture».